Práticas de currículo em escolas ribeirinhas da área de Porto Velho, RO: saberes locais e conhecimentos científicos - Sousa, Domingas Luciene Feitosa (2023)
This thesis, entitled curriculum practices in riverside schools in the Porto Velho-RO area: local knowledge and scientific knowledge, sought to critically analyse curriculum practices in riverside schools, focusing on the relationship between the local knowledge and scientific knowledge, aiming to contribute to the strengthening of school quality in the riverside area. It is important to understandlocal knowledge and its relationship with the school curriculum, seeking tounderstand the culture and curriculum practices in riverside schools in theAmazon, with their different and often invisible world views. The research is linkedto the Curriculum, Knowledge and Culture Research Line of the GraduateProgram in Education: Curriculum at PUC-SP. The theoretical framework has thecontribution of the author's Arroyo (2013a, 2013b), Candau e Moreira (2008), Casali (2001,2004,2018), Casali e Pereira (2016),Cortella(2016), Cury(2018), Freire (2013), Geertz (1989, 2001, 2014), Gimeno Sacristán (2007, 2013, 2017), Hall (2015, 2016), Loureiro (1995), Santos (1986,2007), Santos Douglas (2020),Torres Santomé (2011,2013), among others that deal with the curriculum and local knowledge. The methodology chosen was the participant observation, with emphasis on the Method Ethnographic based on Chizzotti (1992,2017); André (2012), with the development of document analysis, application of questionnaires, and interviews. After that, we used content analysis in Chizzotti (2014), and the Nvivo11 software was also used to intensify the results of the analyses. The methodological proposal had the participation of residents of the communities of Calama, São Carlos and Vila Nova do Teotônio, teachers, managers, supervisors and technicians from the Municipal Department of Education, Division of Rural Education. The results point out that the curricular practice offered at schools from communities’ riverside follows the same guidelines of the urban schools, being, therefore, adopting an urban-centric model, where at the same time, the invisibility of the knowledge, in their practices,remains. As for the curriculum, although the schools follow a framework, it is possible to perceive different models and the practices developed do not contemplate local knowledge, despite the legislation and official documents signalling the possibility of including this knowledge in the pedagogical planning.However, more specific guidelines were not found in the current documents aimed at the inclusion of said knowledge, which allows us to say that there is a lack of knowledge of this prioritization regarding knowledge and the textbook remains as the reference at school, as it presents in organized way skills and competences